The Practice of Vocabulary Drilling Method Used in Teaching and Learning Speaking at Mazroatul Lughoh Islamic Boarding School - Dewi, Fatqu; Syifaul Fahmi, Fajar (Indonesian Journal of Multidisciplinary Educational Research, 2024)
This study aimed to analyze the learning using the drilling vocabulary method in teaching speaking at the Egypt class of Mazroatul Lughoh Islamic Boarding School Pare Kediri. The approach of this study was qualitative research. It involved me as the researcher, the education of Mazroatul Lughoh, and eight students of the Egypt Class of Mazroatul Lughoh Islamic Boarding School Pare Kediri. The steps of this study were survey, planning the actions, implementing and observing the actions, and reflecting on the actions done. The data of this study was qualitative. The qualitative data were obtained by observing the teaching and learning process. The data were collected in the form of field notes and questionnaire transcripts. To ensure trustworthiness, investigators, time, and theoretical triangulation were used. Democratic, process, outcome, catalytic, and dialogic validity were also employed to meet the validity and reliability of the data. The research findings showed that the drilling vocabulary method in teaching speaking had many benefits in learning to speak in the classroom. The drilling vocabulary method constituted a method that applied repetition in pronouncing some vocabulary with the correct pronunciation and articulation. It also gave the Indonesian translation and practice with the topic related to the vocabulary.